Toward a Metagenomic Understanding on the Bacterial Composition and Resistome in Hong Kong Banknotes - Heshiki, Yoshitaro; Dissanayake, Thrimendra; Zheng, Tingting; Kang, Kang; Yueqiong, Ni; Xu, Zeling; Sarkar, Chinmoy; Woo, Patrick C. Y.; Chow, Billy K. C.; Baker, David; Yan, Aixin; Webster, Christopher J.; et al. (Frontiers in Microbiology, 2017)
Currency is possibly one of the main media transmitting pathogens and drug resistance due to its wide circulation in daily life. In this study, we made a comprehensive characterization of the bacterial community present on banknotes collected from different geographical regions of Hong Kong (HK) by performing in vitro characterization of the bacterial presence and resistome profile, as well as metagenomic analysis including microbial diversity, the prevalence of potential pathogens, the dissemination potential of antibiotic resistance genes, among others. When comparing the bacterial community of HK banknotes with other HK environmental samples, including water and marine sediment, we revealed that HK banknotes cover nearly 50% of total genera found in all the environmental samples, implying that banknotes harbor diverse bacteria originated from a variety of environments. Furthermore, the banknotes have higher abundance of potential pathogenic species (~5 times more) and antibiotic resistance genes (~5 times more) with higher dissemination potential (~48 times more) compared with other environmental samples. These findings unveiled the capabilities of this common medium of exchange to accommodate various bacteria, and transmit pathogens and antibiotic resistance. Furthermore, the observed independence of microbiome profile from the city’s topological indices led us to formulate a hypothesis that due to their high circulation banknotes may harbor a homogenized microbiome.